Early de-cannulation from extracorporeal membrane oxygenation following ventricular tachycardia radiofrequency ablation - Sabbag, Avi; Nissan, Johnatan; Beinart, Roy; Sternik, Leonid; Kassif, Igal; Kogan, Alexander; Ram, Eilon; Nof, Eyal (Frontiers in Cardiovascular Medicine, 2022)
Objectives: Ventricular tachycardia ablation (VTA) with hemodynamic compromise presents a challenge. Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) support allows safe completion of the procedure. There is limited data regarding the safety of weaning off VA-ECMO at the end of the procedure. We report our experience with early VA-ECMO de-cannulation after VTA. Methods: All patients undergoing VA-ECMO assisted VTA, between 1.2013 and 12.2020 at a large tertiary center were included. Clinical characteristics, history of arrhythmia, procedural details and outcomes were collected prospectively. Patients weaned from VA-ECMO immediately at the end of the procedure were compared to those that were de-cannulated at a later time. Results: A total of 46 patients (93.5% male, age 62±10 years) were ablated with VA-ECMO support. Most had ischemic cardiomyopathy (65%) and (70%) presented with VT storm. The clinical VT was induced in the majority of patients (76%). A total of 99 VTs were induced of which 76 (77%) were targeted and successfully ablated. Non inducibility was achieved in 74% of cases and most patients (83%) were de-cannulated at the end of the procedure on the procedure table. Survival at 1 year was higher among patients de-cannulated early [86 vs 38% (log rank p value <0.001)]. At one year of follow up, 91.3% of surviving patients were free of appropriate ICD shocks. Conclusion: De-cannulation from VA-ECMO may be done immediately at the conclusion of VTA in most cases. Failure to wean off VA-ECMO is a strong predictor of mortality.